Structural properties and corrosion resistance of tantalum nitride coatings produced by reactive DC magnetron sputtering. Issue 92 (19th September 2016) - Alishahi, M.; Mahboubi, F.; Mousavi Khoie, S. M.; Aparicio, M.; Lopez-Elvira, E.; Méndez, J.; Gago, R.
Abstract : There is a correlation between the corrosion resistance, structure, roughness and the porosity of TaN sputtered films. Abstract : In this study, tantalum nitride (TaN) thin films were deposited on Si(100) and 316L stainless steel (SS) substrates by reactive DC magnetron sputtering. The effect of the nitrogen fraction ([N2 ]) in the gas mixture on the composition, phase formation, roughness and corrosion resistance was investigated. The films were characterized by Rutherford backscattering spectrometry (RBS), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS) and atomic force microscopy (AFM). The results reveal a transition from Ta2 N to N-rich phases by increasing [N2 ] from 2 to 50%, with a dominance of cubic TaN (c-TaN) at intermediate values (5–20%). Moreover, the surface roughness for films with a c-TaN structure is significantly higher. Potentiodynamic polarization and electrochemical impedance spectroscopy (EIS) were also employed to evaluate the corrosion behavior of bare and coated SS. The results show that all TaN films increase the corrosion resistance of SS, irrespective of their bonding structure, which is attributed to the formation of a protective surface oxide layer. However, films with a c-TaN structure deposited at [N2 ] ∼20% provide higher protection efficiency (∼93%), which can be related to a lower density of pinhole defects as derived from the EIS analysis.